Orthosis of the Shoulder Muscles In Terms of Their Electrical Activity as an Indicator to Improve Their Functional Condition in Weightlifters with Muscle Tear after Rehabilitation - Al-Lami , Dr. Nateq Abdul-Rahman Waritha (International Journal of Psychosocial Rehabilitation, 2020)
— The study aimed to measure the electrical activity of shoulder muscles for lifters with muscle rupture after their rehabilitation, and to identify the evaluation of shoulder muscles in terms of their electrical activity as an indicator to improve their occupational status among weightlifters with muscle rupture after their rehabilitation, and the researchers adopted the descriptive research method of scanning a sample of male lifters in The different clubs of Maysan governorate, aged (17-19) years after completing the physical therapy stage for a period of (5-7) days, whose number is (62) injured, who were deliberately selected at a rate (84.932%) of the parent community, and they are those who go to the Physiotherapy Division in a hospital Chest a For a year within the formations of the Maysan Health Department during a period of six months, the researchers were able to collect them procedurally after coordinating with the hospital to conduct electrical planning measurements for the shoulder muscles, and the homogeneity of the research sample was verified in some variables that unite their characteristics, and examined them with the electrical muscle planning device (EMG) clinical type And the treatment of their results statistically with the (SPSS) program, and (6) specific criteria were derived for their evaluation after processing the results of this measurement, and the researchers concluded that it is not possible to rely on the results of modern systems technology to measure the functional improvement of the muscles in evaluating the state of the weight lifter unless the approved levels are approved It is an indication of its results, and that the measurement used by the two researchers achieved reliable and standardized levels in evaluating the functional improvement of the muscles after their rehabilitation.